The Effect of Role Playing Technique on Students Speaking Ability - Ashari P Swondo (Universitas Potensi Utama, 2018)
This study attempted to investigate the effect of role playing technique on student’s speaking ability. The purpose of the study is to find out whether or not there is a significant effect of the technique. The population of this study was 72 students of Potensi Utama University which located at Jl.K.L.Yos Sudarso, Km. 6,5 No. 3A Tanjung Mulia Medan. From this population, two groups were chosen randomly as sample by using lottery system, namely: The control group and experimental group. The total number of sample was 30 students. The instrument used for collecting data was oral test. The scoring system based on a rating system in which a short description on the student’s performance in a scale. In order to see whether or not there is a significant effect between the two techniques, the result of the tests were analyzed tatistically by using the t–test. From the calculation, it is obtained that t–observed is higher than t–critical value. It means that the hypothesis is accepted. In other words, it can be concluded that the role-playing technique significantly influenced the students’ speaking ability in English.